Safety of iron hydroxide adipate tartrate as a novel food pursuant to Regulation (EU) 2015/2283 and as a source of iron in the context of Directive 2002/46/EC. (10th December 2021) - ,; Turck, Dominique; Bohn, Torsten; Castenmiller, Jacqueline; De Henauw, Stefaan; Ildico Hirsch‐Ernst, Karen; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; Pentieva, Kristina; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on iron hydroxide adipate tartrate as a novel food (NF) pursuant to Regulation (EU) 2015/2283 and as a source of iron in the context of Directive 2002/46/EC. The NF is intended to be used in food supplements up to a maximum dose of 100 mg per day, corresponding to a maximum daily intake of iron of 36 mg. The target population proposed by the applicant is the general population above 3 years of age. The NF which is the subject of the application is an engineered nanomaterial having primary particles, of almost spherical morphology, with a diameter typically smaller than 5 nm. The studies provided for absorption, distribution, metabolism and excretion (ADME) and bioavailability indicate that iron, once taken up into the epithelial cells of the gut, is subject to the same mechanisms of regulation and absorption as that of other forms of iron. Further studies provided in the context of the toxicological assessment indicate that the NF does not lead to iron bioaccumulation in tissues and organs at the doses tested. The Panel notes that the NF contains nickel at concentrations that may increase the risk of flare‐up reactions in nickel‐sensitised young individuals up to 10 years of age. In the 90‐day toxicity study, findings related to haematology, clinical biochemistry and organ weights were observed and the Panel defined a no observed adverse effect level (NOAEL) of 231 mg/kg body weight (bw) per day, that is, the mid‐dose used in the study. The Panel considers that the NF is a source from which iron is bioavailable and it is safe under the proposed conditions of use.